2020
DOI: 10.3390/ijerph17103460
|View full text |Cite
|
Sign up to set email alerts
|

Let Nature Be Thy Medicine: A Socioecological Exploration of Green Prescribing in the UK

Abstract: Prescribing nature-based health interventions (green prescribing)—such as therapeutic horticulture or conservation activities—is an emerging transdisciplinary strategy focussed on reducing noncommunicable diseases. However, little is known about the practice of, and socioecological constraints/opportunities associated with, green prescribing in the UK. Furthermore, the distribution of green prescribing has yet to be comprehensively mapped. In this study, we conducted a socioecological exploration of green pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 74 publications
(80 reference statements)
4
51
0
1
Order By: Relevance
“…The Department for Health and Social Care [ 9 ] observed that “prevention and early intervention programmes represent very good value for money” in that poor health and well-being can be improved while at the same time taking cost and pressure away from primary and secondary health and public service systems. There are high levels of satisfaction with social and green prescribing [ 63 , 66 ], but it also important that these programmes do not become a reason for cutting public services. We conclude that nature-based and mind–body interventions can play an important role in helping to achieve these aspirations, particularly in a post-Covid-19 world, where economic and social stresses on individuals and health systems will be higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Department for Health and Social Care [ 9 ] observed that “prevention and early intervention programmes represent very good value for money” in that poor health and well-being can be improved while at the same time taking cost and pressure away from primary and secondary health and public service systems. There are high levels of satisfaction with social and green prescribing [ 63 , 66 ], but it also important that these programmes do not become a reason for cutting public services. We conclude that nature-based and mind–body interventions can play an important role in helping to achieve these aspirations, particularly in a post-Covid-19 world, where economic and social stresses on individuals and health systems will be higher.…”
Section: Discussionmentioning
confidence: 99%
“…The NASP notes that SP is part of an aim to prescribe bespoke personalized medical and social interventions, but also note that health improvements may be “long slow journeys” for many patients. The term green prescribing has been used to refer to the nature-based options available to SP operations [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buffer sizes of 10 m, 25 m, 50 m, and 100 m were considered appropriate for the study scale. Similar distances have been used in previous green space and epidemiology studies ( 31, 7072 ). A 100 m maximum buffer radius was chosen; at greater distances, effects would no longer be local to the sampling points (i.e., they would overlap with other sampling points).…”
Section: Methodsmentioning
confidence: 99%
“…Do people who lie down or work close to the ground (e.g., gardeners bending over to dig) have different exposure levels to those who remain upright, and what are the downstream implications for health? Developing a refined understanding of this aerobiome-human interface could also have implications for the design and monitoring of nature-based health interventions, for example via green/nature prescribing (Robinson and Breed 2019;Shanahan et al 2019;Robinson et al 2020). Furthermore, protocols for sampling the aerobiome to date have often included a reasonable yet arbitrary sampling height of 2 m (Airaudi and Marchisio et al 1996;Cordeiro 2010;Mhuireach et al 2016;Domingue 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Developing a refined understanding of this aerobiome–human interface could also have implications for the design and monitoring of nature-based health interventions, for example via green/nature prescribing ( Robinson and Breed 2019 ; Shanahan et al. 2019 ; Robinson et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%